Pengembangan Antarmuka Pengguna (User Interface) Sistem Pengelolaan Beasiswa Berbasis Website dengan Pendekatan Cognitive Walkthrough - Tasya, Selviana; Setyantoro, Dwipo (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
An effective user interface (UI) is crucial in a web-based scholarship management system to ensure a good user experience and easy accessibility to information. However, many users still encounter difficulties using the existing system, necessitating a better design. This study aims to evaluate and improve the user interface of the scholarship management system using the Cognitive Walkthrough approach. The Cognitive Walkthrough approach is used to identify usability issues in the user interface. A prototype of the design solution was then tested through usability testing involving seven evaluators and five different task scenarios using Maze. The results show that all evaluators were able to complete the task scenarios with a category 1 rating (no issues), although four evaluators experienced minor issues in task scenarios 1 and 2. Evaluators were slightly confused when searching for the latest requirements information and the ineffective use of buttons. By implementing the suggested improvements based on the findings from the Cognitive Walkthrough, the user interface in the scholarship management system can be significantly enhanced, facilitating users in accessing the required information.